Applicability of TiO2‐Laden Asphalt Pavements in Reducing the Vehicular Pollution of Chandigarh, India. Issue 5 (2nd March 2022) - Singh, Harjinder; Thind, Parteek Singh; Singh, Sandeep; John, Siby
Abstract: Vehicular emissions play a significant role in urban‐environmental pollution. Therefore, in the present investigation, efforts are made to estimate the applicability of Titanium dioxide (TiO2 )‐laden asphalt pavements in degrading the ambient Nitrogen Dioxide (NO2 ) in Chandigarh, India. In this regard, an artificial environment is created, and experiments are designed to degrade NO2 and Sulfur dioxide (SO2 ) using photocatalysis. Further, the process parameters, viz., concentration of TiO2 emulsion (25 to 125 mL m −2 ), Ultraviolet UV‐A irradiance (1 to 5 mW cm −2 ), and proportion of bitumen (4 to 6%), are optimized to achieve the maximum degradation of NO2 and SO2 . Results reveal that maximum degradation of NO2 and SO2, that is, 61.91 and 55.39%, respectively, is achieved at 81.67 mL m −2 of TiO2 emulsion, 5 mW cm −2 of UV‐A irradiance, and 5.78% of bitumen. The optimized conditions of photocatalytic application are further used to treat the ambient NO2 of Chandigarh, India. Analysis of the ambient air data of Chandigarh, India, from 2005 to 2015, depicts significant contribution of vehicular emissions. It is also predicted that by 2031 the ambient concentration of NO2, may exceed the permissible limits. However, layering of asphalt payments with TiO2 could prevent such situation by 2114. Abstract : An emulsion of TiO2 is sprayed on the surface of asphalt roads and maximum degradation of pollutant gases such as NO2 and SO2 is estimated. Further, it is also established that spraying TiO2 on asphalt roads of urban areas may assist in reducing the concentration of ambient NO x .